Eustachijaus ir Emilijos Vrublevskių bibliotekos bičiulių draugija (1936–1939) ir jos veikėjai - (:unkn) unknown (My University, 2015)
Eustachijaus ir Emilijos Vrublevskių bibliotekos bičiulių draugija veikė 1936–1939 m., Antrojo pasaulinio karo išvakarėse ji turėjo daugiau nei šimtą narių. Draugijos nariais buvo daugiausia Stepono Batoro universiteto Vilniuje bei kitų mokslo ir švietimo įstaigų darbuotojai, bibliotekininkai, kunigai, kariškiai, teisininkai. Didžioji dalis – lenkų tautybės asmenys, bet buvo ir lietuvių, karaimų, baltarusių. Draugijai vadovavo valdyba, kurios pirmininkas buvo kun. Pranciškus Tičkovskis (Franciszek Tyczkowski, 1891–1982). Draugijos tikslas – remti Valstybinę Eustachijaus ir Emilijos Vrublevskių biblioteką, skatinti visuomenės susidomėjimą bibliotekos darbu, rinkti lėšas jos reikmėms, ypač leidybai ir mokslo tyrinėjimams. Dėl to jos nariai Vrublevskių bibliotekai patys aukojo pinigus, knygas, rankraščius ir muziejinius daiktus bei skatino tą daryti asmenis, nepriklausiusius draugijai. Taip pat jie organizuodavo koncertus, parodas, minėjimus, o surinktas lėšas atiduodavo bibliotekos reikmėms. Draugijos veikla nutrūko Antrojo pasaulinio karo metais. Per trumpą savo egzistavimo laiką ji prisidėjo prie sėkmingos Valstybinės Vrublevskių bibliotekos Vilniuje plėtros, ugdė visuomenės atsakingumo jausmą už šios bibliotekos bei kitų mokslo ir kultūros įstaigų likimą.

The aim of this article is to briefly overview the establishment and activities of the Society of the Friends of the Wroblewski Library (Towarzystwo Przyjaciół Biblioteki im. Eustachego i Emilii Wróblewskich) and to characterize its most active members. This society was active in 1936–1939 and its activities have not been well studied yet. This article is based on archive materials, contemporary press publications and articles of Polish authors. This successful society was established in 1936 owing to an initiative of Stefan Burhardt (1899–1991), director of the Wroblewski Library. Before World War II, there had been more than a hundred members. Members of this society were mostly from Stephen Batory University and other educational institutions, and also included librarians, priests, lawyers etc. Most of them were Poles, but there also were Lithuanians, Karaims and Byelorussians. The Council’s Head of the society was priest Franciszek Tyczkowski (1891–1982). The purpose of the society was to support the development of the Wróblewski Library, to keep up public interest in the library, and to collect money for editorial and scientific activities. Members of the society donated money, books, manuscripts and museum artifacts to the Wroblewski Library and encouraged non-members to do the same. The society also organized concerts, exhibitions and celebrations, of which the profits were given to the Wroblewski Library. The activities of the society were interrupted by the start of World War II. During the brief time of its existence this society has been successfully supporting the activities of the Wróblewski library and promoting responsibility for this library and other scientific and cultural institutions.
The Society of the Friends of the Eustachy and Emilia Wroblewski Library (1936–1939) and Its Personalities
Moksliniai straipsniai / Scientific articles
Keywords: Eustachijaus ir Emilijos Vrublevskių bibliotekos bičiulių draugija; Valstybinė Vrublevskių biblioteka; Vilniaus bibliotekos; Tadas Vrublevskis; Pranciškus Tičkovskis; Stefanas Burhardtas; Helena Drège